Temperatura em caixa de isopor para refrigeração de sêmen bovino descongelado - Pimentel, Paulo Ricardo Costa (Brasil, 2023)
The IATF is a reproductive biotechnology widely used in regions with high cattle production. However, in the state of Amazonas, this technique is not widely spread, mainly due to difficulties in accessing technology, logistics, and costly expenses associated with the acquisition and maintenance of semen tanks, for example. In this regard, this study aimed to evaluate the cooling temperature curve for thawed bovine semen in Styrofoam boxes at temperatures of 5 ±1°C and 15 ±1°C, with the intention of finding an alternative system for cooling and preserving semen until its field use. Two 17 L Styrofoam boxes were used, with 4 reusable ice packs (750ml) to maintain a temperature of 5±1°C and 2 reusable ice packs (990ml) to maintain a temperature of 15±1°C. A digital thermometer with a sensor was attached to collect internal temperature data in each box. Two treatments, 5±1°C and 15±1°C, were evaluated with repeated measurements over time. The results were analyzed descriptively. The cooling and stabilization rates were -0.4867 °C/minute and 0.0035°C/minute for the ±5°C treatment, and -0.8167 °C/minute and 0.0086°C/minute for the 15±1°C treatment, respectively. The 5±1°C box maintained the stabilization temperature for 570 minutes (9.5 hours), and the 15±1°C box maintained the stabilization temperature for 210 minutes (3.5 hours). The alternative semen preservation systems tested in this study are low-cost, and the preservation time achieved in the 5°C box allows for satisfactory and feasible transportation and preservation of semen for field applications of this technology.